“Cylinder seals for the lower classes”: Ein Merkmal der Provinzkultur des ausgehenden Alten Reiches? - Willems, Harco (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
Egyptologists have paid much attention to inscribed administrative seals and their impressions. By contrast, the so-called figure seals, which render no or hardly any text, but instead use icons and signs inspired on hieroglyphs which however yield no coherent sense, have received far less attention. Usually this material is related to the lower strata of society. According to current interpretations, it is rooted in the Egyptian culture of the later Old Kingdom and First Intermediate Period. The phenomenon would be a corollary of the decreasing prominence of central state authority in this era. Proceeding from a number of recent early Old Kingdom finds from al-Shaykh Saʽīd/Wādī Zabaydā, the present article argues that a) figure seals were continually in use from the late Predynastic until the late Old Kingdom and b) different from what is commonly assumed, stamp seals were in existence long before the late Old Kingdom. The article challenges the relationship between these object categories and developments specifically in late Old Kingdom Egypt.